Differentiation of the brain vasculature: the answer came blowing by the Wnt - Liebner, Stefan; Plate, Karl H (Vascular Cell, 2010)
Abstract   Vascularization of the vertebrate brain takes place during embryonic development from a preformed perineural vascular plexus. As a consequence of the intimate contact with neuroectodermal cells the vessels, which are entering the brain exclusively via sprouting angiogenesis, acquire and maintain unique barrier properties known as the blood-brain barrier (BBB). The endothelial BBB depends upon the close association of endothelial cells with pericytes, astrocytes, neurons and microglia, which are summarized in the term neuro-vascular unit. Although it is known since decades that the CNS tissue provides the cues for BBB induction and differentiation in endothelial cells, the molecular mechanism remained obscure.   Only recently, the canonical Wnt/β-catenin pathway and the Wnt7a/7b growth factors have been implicated in brain angiogenesis on the one hand and in BBB induction on the other. This breakthrough in understanding the differentiation of the brain vasculature prompted us to review these findings embedded in the emerging concepts of Wnt signaling in the vasculature. In particular, interactions with other pathways that are crucial for vascular development such as VEGF, Notch, angiopoietins and Sonic hedgehogare discussed. Finally, we considered the potential role of the Wnt pathway in vascular brain pathologies in which BBB function is hampered, as for example in glioma, stroke and Alzheimer's disease.